Maxillary Premolars with Three Root Canals: A Case Report - Beyraghshamshir, Reza; Karimian, Elnaz; Sekandari, Salehe (Iranian Endodontic Journal, 2020)
The numerous difficulties found during root canal treatments are due to anatomical variations in the radicular morphology. Maxillary premolars have highly varied root canal systems and shapes. This case report addresses two endodontic treatment cases of the maxillary first and second premolars with three canals and a summary of their anatomical forms. The article describes the diagnosis and clinical management of these teeth.